2014
DOI: 10.1038/onc.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

miR-506 acts as a tumor suppressor by directly targeting the hedgehog pathway transcription factor Gli3 in human cervical cancer

Abstract: Although significant advances have recently been made in the diagnosis and treatment of cervical carcinoma, the long-term survival rate for advanced cervical cancer remains low. Therefore, an urgent need exists to both uncover the molecular mechanisms and identify potential therapeutic targets for the treatment of cervical cancer. MicroRNAs (miRNAs) have important roles in cancer progression and could be used as either potential therapeutic agents or targets. miR-506 is a component of an X chromosome-linked mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 30 publications
10
84
0
Order By: Relevance
“…In the present study, we demonstrated the critical role of miR-506 in cervical cancer. Our results were consistent with those of a recent study that reported that miR-506 is significantly downregulated in cervical cancer tissues (42). These authors further demonstrated that miR-506 overexpression suppressed the growth and enhanced apoptosis and chemosensitivity of cervical cancer cells by targeting Gli3 (42).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, we demonstrated the critical role of miR-506 in cervical cancer. Our results were consistent with those of a recent study that reported that miR-506 is significantly downregulated in cervical cancer tissues (42). These authors further demonstrated that miR-506 overexpression suppressed the growth and enhanced apoptosis and chemosensitivity of cervical cancer cells by targeting Gli3 (42).…”
Section: Discussionsupporting
confidence: 83%
“…Our results were consistent with those of a recent study that reported that miR-506 is significantly downregulated in cervical cancer tissues (42). These authors further demonstrated that miR-506 overexpression suppressed the growth and enhanced apoptosis and chemosensitivity of cervical cancer cells by targeting Gli3 (42). Overall, decreased miR-506 expression may result in the overexpression of oncogenes, such as FOXQ1, which contributes to the development and progression of cervical cancer.…”
Section: Discussionsupporting
confidence: 82%
“…Li et al (27) reported that the overexpression of miR-342-3p inhibits cell proliferation, migration and invasion in cervical cell lines by targeting mammalian transcription factor forkhead box M1. Wen et al (28) reported that miR-506 induced cell cycle arrest at the G1/S transition, enhanced the apoptosis and chemosensitivity of cervical cancer cells, and inhibited cervical cancer growth in vitro and in vivo. Data from the current study provides evidence that miR-138 can inhibit proliferation, colony formation, migration and invasion, induce cell apoptosis in cervical cancer cells, and suppress tumor growth in nude mice models.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was demonstrated that miR-506 functions as a tumor suppressor in neuroblastoma by directly targeting ROCK1. Previous studies have reported that the expression of miR-506 is reduced in numerous types of cancer, including epithelial ovarian cancer (15)(16)(17)(18), hepatocellular carcinoma (19), cervical cancer (20), lung cancer (21), breast cancer (22) and colon cancer (23), and is involved in cancer progression, notably cell proliferation, metastasis and apoptosis. In the current study, it was observed that miR-506 was decreased in neuroblastoma tissues and cell lines when compared to normal tissues, supporting the notion that miR-506 functions as a potential tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results demonstrated that miR-506 inhibited neuroblastoma cell proliferation and metastasis. The previously reported target genes of miR-506 include cyclin-dependent kinase4/6-forkhead box protein M1 (18), yes-associated protein (19), GLI family zinc finger 3 (20), nuclear factor-κB p65 (21) and others. In the present study, it was verified that ROCK1 was a novel target gene for miR-506 in neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%